2013
DOI: 10.5966/sctm.2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Autologous Bone Marrow-Derived Mesenchymal Stem Cell Injections Improve Radiation-Induced Proctitis in Pigs

Abstract: The management of proctitis in patients who have undergone very-high-dose conformal radiotherapy is extremely challenging. The fibrosis-necrosis, fistulae, and hemorrhage induced by pelvic overirradiation have an impact on morbidity. Augmenting tissue repair by the use of mesenchymal stem cells (MSCs) may be an important advance in treating radiation-induced toxicity. Using a preclinical pig model, we investigated the effect of autologous bone marrow-derived MSCs on high-dose radiation-induced proctitis. Irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 41 publications
1
82
0
2
Order By: Relevance
“…aMSCs are promising for cellular therapies due to their prominent anti-inflammatory effects, enhancing IL-10 secretion, ease of isolation, high cell count after expansion, as well as their source abundance [73]. In radiation-induced normal tissue injury, aMSCs have shown significant repair of cutaneous radiation syndrome [79][80][81][82][83] and photo-aging [84], RT-induced acute salivary gland [85] and intestine injuries [70,[86][87][88], and chronic injuries induced by radiotherapy [80,89]. In addition, we have shown in a previous study that aMSCs are relatively resistant to ionizing radiation, a property that qualifies them to be a reliable cellular therapy candidate before and during RT [159].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…aMSCs are promising for cellular therapies due to their prominent anti-inflammatory effects, enhancing IL-10 secretion, ease of isolation, high cell count after expansion, as well as their source abundance [73]. In radiation-induced normal tissue injury, aMSCs have shown significant repair of cutaneous radiation syndrome [79][80][81][82][83] and photo-aging [84], RT-induced acute salivary gland [85] and intestine injuries [70,[86][87][88], and chronic injuries induced by radiotherapy [80,89]. In addition, we have shown in a previous study that aMSCs are relatively resistant to ionizing radiation, a property that qualifies them to be a reliable cellular therapy candidate before and during RT [159].…”
Section: Methodsmentioning
confidence: 99%
“…aMSCs have been investigated in many studies for cutaneous radiation syndrome [79][80][81][82][83] and photo-aging [84] with significant tissue repair. aMSCs systemic cell therapy led to significant restoration and improvement of acute salivary gland [85] and intestine injuries [70,[86][87][88] induced by ionizing radiation (IR). Furthermore, aMSCs have shown promise for successful cell therapy in chronic radiotherapy-induced injuries [80,89].…”
Section: Mesenchymal Stromal/stem Cells Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These immunomodulatory properties of MSCs are of special importance in the treatment of IBD. Systemic administration of bone marrow MSCs in a mouse model of chemical-induced colitis [43] and in a pig model of radiation-induced proctitis [44] , down-regulated autoimmune and inflammatory responses, and as a consequence, facilitated tissue regeneration. The experience in luminal CD is limited (Table 2).…”
Section: Mesenchymal Stem Cell Transplantationmentioning
confidence: 99%
“…The limitations of radiotherapy, in particular radiation injury to the gastrointestinal tract, have produced an urgent requirement for novel and effective treatments for radiation damage (2). Previous studies have shown that mesenchymal stem cells (MSCs) are able to promote the repair of intestinal structures and functions, indicating their potential for the treatment of intestinal radiation injury (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%